MiR-146a-5p deficiency in extracellular vesicles of glioma-associated macrophages promotes epithelial-mesenchymal transition through the NF-κB signaling pathway - Chao Xu; Pan Wang; Haiyan Guo; Chuan Shao; Bin Liao; Sheng Gong; Yanghao Zhou; Bingjie Yang; Haotian Jiang; Gang Zhang; Nan Wu (Cell Death Discovery, 2023)
Abstract Glioma-associated macrophages (GAMs) are pivotal chains in the tumor immune microenvironment (TIME). GAMs mostly display M2-like phenotypes with anti-inflammatory features related to the malignancy and progression of cancers. Extracellular vesicles derived from immunosuppressive GAMs (M2-EVs), the essential components of the TIME, greatly impact the malignant behavior of GBM cells. M1- or M2-EVs were isolated in vitro, and human GBM cell invasion and migration were reinforced under M2-EV treatment. Signatures of the epithelial-mesenchymal transition (EMT) were also enhanced by M2-EVs. Compared with M1-EVs, miR-146a-5p, considered the key factor in TIME regulation, was deficient in M2-EVs according to miRNA-sequencing. When the miR-146a-5p mimic was added, EMT signatures and the invasive and migratory abilities of GBM cells were correspondingly weakened. Public databases predicted the miRNA binding targets and interleukin 1 receptor-associated kinase 1 (IRAK1) and tumor necrosis factor receptor-associated factor 6 (TRAF6) were screened as miR-146a-5p binding genes. Bimolecular fluorescent complementation and coimmunoprecipitation confirmed interactions between TRAF6 and IRAK1. The correlation between TRAF6 and IRAK1 was evaluated with immunofluorescence (IF)-stained clinical glioma samples. The TRAF6-IRAK1 complex is the switch and the brake that modulates IKK complex phosphorylation and NF-κB pathway activation, as well as the EMT behaviors of GBM cells. Furthermore, a homograft nude mouse model was explored and mice transplanted with TRAF6/IRAK1-overexpressing glioma cells had shorter survival times while mice transplanted with glioma cells with miR-146a-5p overexpression or TRAF6/IRAK1 knockdown lived longer. This work indicated that in the TIME of GBM, the deficiency of miR-146a-5p in M2-EVs enhances tumor EMT through disinhibition of the TRAF6-IRAK1 complex and IKK-dependent NF-κB signaling pathway providing a novel therapeutic strategy targeting the TIME of GBM.